Administration of a polyphenol-enriched feed to farmed sea bass (Dicentrarchus labrax L.): Kidney melanomacrophages response. Issue 68 (September 2017) - Arciuli, Marcella; Fiocco, Daniela; Fontana, Sergio; Arena, Mattia Pia; Frassanito, Maria Antonia; Gallone, Anna
Abstract: The reinforcement of the defense mechanism of fish, through the administration of immunostimulants, is considered as a promising alternative to vaccines. Natural immunostimulants such as polyphenols, flavanoids, pigments and essential oils can modulate the innate immune response. In lower vertebrates, melano-macrophage centres, i.e. clusters of pigment-containing cells forming the extracutaneous pigment system, are wide-spread in the stroma of the haemopoietic tissue, mainly in kidney and spleen. In fishes, melano-macrophage centres play an important role in the immune response against antigenic stimulants and pathogens. In the present study, we evaluated the effect of a polyphenol-enriched diet on the health status of European sea bass (Dicentrarchus labrax L.). Farmed sea bass were administered a feed containing a phytocomplex, rich in catechins and epigallocatechins, which was obtained from the seeds of Canosina Nero di Troia Vitis vinifera and mixed with conventional feed at two different concentrations. The effects of such a diet were investigated in juvenile and commercial size samples, i.e. undergoing a short- and long-term period of diet, respectively, focusing on their extracutaneous pigmentary system and, in more detail, on the enzymatic activities leading to melanin biosynthesis. Our results show that prolonged dietary treatments with higher concentration of polyphenols might modulate tyrosinase activity and gene expression in commercial size fishes. An increase of melano-macrophage activity is correlated to a stimulation of cytoprotective functions against antigenic stimulants and pathogens, as an expression of a robust and protective adaptive immune response. Highlights: Dietary administration of grape polyphenols stimulates tyrosinase activity of kidney melanomacrophages in adult sea bass. Tyrosinase genes RNA expression is detected in the kidney of farmed adult sea bass, though at a lower level than in skin. A polyphenol-enriched diet up-regulates tyrosinase genes transcription in the kidney of farmed adult sea bass.